1996
DOI: 10.1021/bi951535l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Electrostatic and Nonelectrostatic Components of Protein−Membrane Binding Interactions

Abstract: A general method was developed to determine the thermodynamic parameters for the interaction of protein with membranes. Protein intrinsic tryptophan fluorescence was quenched by titration with large unilamellar vesicles containing 9,10-dibrominated distearoylphosphatidylcholine (Br4-DSPC) or a small amount of trinitrophenylphosphatidylethanolamine (TNP-PE), Binding was modeled as a bimolecular reaction of free protein with a unit of "n" lipid molecules and a dissociation constant, Kd. The contribution of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…Previously, membrane binding analysis of the p190H 6 revealed that the dissociation constant (K d ) for membrane association of the His-tagged channel peptide did not vary significantly from the untagged, thermolytic channel domain of WT colicin E1. Also, the binding of WT p190H 6 to anionic LUVs under conditions (pH 4, ionic strength, I ϳ 0.1 M, anionic lipid content ϭ 40%) for which the protein has the highest activity was assayed as described earlier (24,31). The observed binding parameters, n ϭ 32-45 (lipid molecules bound per protein) and K d ϭ 0.8 -1.2 nM, are in good agreement with earlier results for the WT colicin thermolytic channel peptide (24,31).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, membrane binding analysis of the p190H 6 revealed that the dissociation constant (K d ) for membrane association of the His-tagged channel peptide did not vary significantly from the untagged, thermolytic channel domain of WT colicin E1. Also, the binding of WT p190H 6 to anionic LUVs under conditions (pH 4, ionic strength, I ϳ 0.1 M, anionic lipid content ϭ 40%) for which the protein has the highest activity was assayed as described earlier (24,31). The observed binding parameters, n ϭ 32-45 (lipid molecules bound per protein) and K d ϭ 0.8 -1.2 nM, are in good agreement with earlier results for the WT colicin thermolytic channel peptide (24,31).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, changes in entropy (ΔS) and Gibbs free energy (ΔG) can be calculated according to equation [7], which takes into consideration the relationship between the equilibrium constant K and the partition coefficient in terms of the reactant volumes 42 :…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…Equation [7] 0.8 being the specific lipid molar volume (L/mol) 42 . Standard deviations are indicated.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…The interplay of hydrophobicity and electrostatics and their distribution within the polypeptide sequence have only been studied in detail for small peptides (3-5, 7, 13-15, 17-20). In the case of proteins, the role of these effects on the association with and the insertion into membranes are still poorly understood (2,(21)(22)(23)(24).The study of the membrane insertion process of the translocation (T) 1 domain of diphtheria toxin (25) can provide precious insight into the interactions between proteins and membranes and the refolding mechanisms of membrane proteins. During intoxication of cells (25), the toxin reaches the early endosomes through the clathrin-coated pathway (26).…”
mentioning
confidence: 99%
“…The interplay of hydrophobicity and electrostatics and their distribution within the polypeptide sequence have only been studied in detail for small peptides (3-5, 7, 13-15, 17-20). In the case of proteins, the role of these effects on the association with and the insertion into membranes are still poorly understood (2,(21)(22)(23)(24).…”
mentioning
confidence: 99%